Feeling the Heat : Adapting to Climate Change in the Middle East and Central Asia - Duenwald, Christoph (Departmental Papers; Departmental Paper, 2022)
Climate change is among humanity's greatest challenges, and the Middle East and Central Asia region is on the frontlines of its human, economic, and physical ramifications. Much of the region is located in already difficult climate zones, where global warming exacerbates desertification, water stress, and rising sea levels. This trend entails fundamental economic disruptions, endangers food security, and undermines public health, with ripple effects on poverty and inequality, displacement, and conflict. Considering the risks posed by climate change, the central message of this departmental paper is that adapting to climate change by boosting resilience to climate stresses and disasters is a critical priority for the region's economies.